PERANCANGAN MEDIA PEMBELAJARAN PJOK BERBASIS MOBILE MENGGUNAKAN GDEVELOP 5 PADA MATERI SEPAK BOLA KELAS 5 SDN JOGLO SURAKARTA TAHUN PELAJARAN 2025/2026 - Febryan Aji Nur Wahid; Oktiana Handini; Yudhistiro Pandu Widhoyoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The learning process of Physical Education, Sport, and Health (PJOK) on soccer material at SDN Joglo Surakarta has been conducted conventionally, relying solely on direct demonstration without adequate visual media support. This condition made it difficult for fifth-grade students to understand basic soccer techniques such as passing, dribbling, shooting, and stopping in detail. The lack of innovative learning media encouraged the need to develop a more engaging and technology-based alternative that suits students' familiarity with digital devices. Therefore, this study aimed to design a mobile-based PJOK learning media using GDevelop 5 software and to evaluate its feasibility as a supporting medium for soccer learning. This study employed the Research and Development (R&D) method following the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The resulting product is a mobile application named Football Smart Class, operable on Android devices, which contains basic soccer technique materials, movement demonstration videos accessed via QR codes, and practice questions for learning evaluation. Prior to trial, the media underwent functional testing through Black Box Testing, with all features running validly without technical issues. Subsequently, validation was conducted by three experts, namely a media expert, an educator expert, and a coaching expert, who provided scores of 84%, 98%, and 96% respectively. The overall average from the three validators reached 92.66%, placing this learning media in the very feasible category for use in fifth-grade PJOK soccer learning at SDN Joglo Surakarta.